Alloy‐Controlled Work Function for Enhanced Charge Extraction in All‐Inorganic CsPbBr3 Perovskite Solar Cells. Issue 9 (17th April 2018) - Ding, Jie; Zhao, Yuanyuan; Duan, Jialong; He, Benlin; Tang, Qunwei
Abstract: All‐inorganic CsPbX3 (X=I, Br) perovskite solar cells are regarded as cost‐effective and stable alternatives for next‐generation photovoltaics. However, sluggish charge extraction at CsPbX3 /charge‐transporting material interfaces, which arises from large interfacial energy differences, have markedly limited the further enhancement of solar cell performance. In this work, the work function (WF) of the back electrode is tuned by doping alloyed PtNi nanowires in carbon ink to promote hole extraction from CsPbBr3 halides, while an intermediate energy by setting carbon quantum dots (CQDs) at TiO2 /CsPbBr3 interface bridges electron transportation. The preliminary results demonstrate that the matching WFs and intermediate energy level markedly reduce charge recombination. A power conversion efficiency of 7.17 % is achieved for the WF‐tuned all‐inorganic perovskite solar cell, in comparison with 6.10 % for the pristine device, and this is further increased to 7.86 % by simultaneously modifying with CQDs. The high efficiency and improved stability make WF‐controlled all‐inorganic perovskite solar cells promising to develop advanced photovoltaic platforms. Abstract : Back under alloyed control : In all‐inorganic perovskite solar cells, the work function (WF) of the back electrode is tuned by incorporating PtNi nanowires into state‐of‐the‐art carbon paste to reduce the energy difference at the CsPbBr3 /carbon interface. The matching WFs of the back electrode and the intermediate energy level at the TiO2 /CsPbBr3 interface markedly promote charge extraction.